Patients’ Request for Extraction of Tooth and A Review of Its Ethical Implications – A Cross Sectional Survey - Sharmila S (Faculty of Dentistry, Universitas Trisakti, 2024)
Background: Tooth loss leads to functional disability, compromises aesthetics, and reduces quality of life. Tooth mortality reflects untreated dental disease and is considered a crude but useful measure of the dental status of a community. There are many contributing reasons for tooth mortality, and a patient’s individual request for the extraction of teeth is one of them. Objective: The objective of this study was to assess patients’ decisions regarding extraction, the various factors that influence extraction, and its ethical implications. Methods: A cross-sectional survey was conducted among 120 randomly selected subjects visiting the outpatient Department of Oral and Maxillofacial Surgery, Tamil Nadu Government Dental College, Chennai, Tamil Nadu. Data were collected using a self-administered recording form. Descriptive data collected were measured in proportion and percentage. Results: Among the participants, 40 were male, and 80 were female. Based on the dentist’s decision, 78.90% of extractions were carried out, and 21.1% were based on a patient request, despite the choice of alternative treatment being given to them. Pain, problems with mastication, long waiting periods for dental appointments, poor understanding of explanations given by the dentist, and fear of alternative modes of treatment were found to be the reasons for patients’ requests. Pain was found to be the most common reason for the request, followed by problems with mastication and an unaesthetic appearance. Conclusion: Socioeconomic status and education level strongly influence a patient’s request for extraction. Even though alternate strategies instead of extraction were available, considering the patients’ autonomy, treatment was carried out. Educating, motivating, and providing care at the preventive level can reduce irrational requests for tooth extraction.